The role of social media in service promotion in Tanzania: A multiple cases of Vodacom and Tigo communication companies - Chenga, Yvone (Mzumbe University, 2026)
A dissertation submitted in a partial fulfillment of the requirements for award of degree of Master's of Business Administration in Corporate Management(MBA-CM) of Mzumbe University